Absolute oral bioavailability of fenofibric acid and choline fenofibrate in rats determined by ultra‐performance liquid chromatography tandem mass spectrometry. (10th October 2016) - Wei, Xudan; Li, Ping; Liu, Meina; Du, Yuqian; Wang, Menglin; Zhang, Jinling; Wang, Jing; Liu, Hongzhuo; Liu, Xiaohong
Abstract: Choline fenofibrate is the choline salt of fenofibric acid, which releases free fenofibric acid in the gastrointestinal tract. To estimate the absolute oral bioavailability of fenofibric acid and choline fenofibrate, a novel and sensitive UPLC–MS/MS method with liquid–liquid extraction procedure was developed for the determination of fenofibric acid in rat plasma. The separation was achieved on a Phenomenex Kinetex C18 column (50 × 2.1 mm, 2.6 μm) containing 2 mm ammonium acetate–methanol with a gradient elution program. Validations of this method including specificity, sensitivity (limit of quantification, 5 ng/mL), linearity (0.005–10 μg/mL), accuracy (within ±4.3%), precision (intra‐ and inter‐day coefficient of variation <11.3%), recovery (94.9–105.2% for fenofibric acid), matrix effect, stability and dilution, were all within acceptable limits. This method successfully supported the determination of fenofibric acid and choline fenofibrate. The absolute oral bioavailability was 93.4% for choline fenofibrate and 40.0% for fenofibric acid. These results suggested that choline fenofibrate and fenofibric acid had a better in vivo pharmacokinetic behavior than that of fenofibrate. The two new orally administrated pharmaceuticals, fenofibric acid and choline fenofibrate, can be developed as alternatives to fenofibrate.